PENGARUH PERBEDAAN FREKUENSI APLIKASI PESTISIDA NABATI PHYMAR C 711 TERHADAP KESEMBUHAN PENYAKIT BUSUK BATANG DIPLODI (Botryodiplodia theobromae Pat.) PADA TANAMAN JERUK (Citrus reticulata L.) - Gusnawati, Mariadi, Muliana . . (Agriplus, 2014)
The study aimed to evaluate the effect of biopesticide application frequency of Phymar C 711 to diplodia stem rot disease recovery on citrus plant (Citrus reticulata L.). The experiment was conducted in Cialam Jaya, Konda, South Konawe, province of Southeast Sulawesi from September to November 2012. The experiment was arranged in Randomized Complete Block Design with single factor i.e. application frequency of Phymar C 711, consisted of 4 treatments  and 4 replications (16 plots). Each plot consisted of 3 citrus plants, so that 48 citrus plants were needed in the experiment. The treatments were (1). T0: diseased plant control (without Phymar C 711 application), (2). T01: healthy plant control (without Phymar C 711 aplication), (3). T1: Phymar C 711 application with single application, and (4). T2: Phymar C 711 application with double application with interval of 16 days. Variable observed was percentage of diplodia stem rot disease recovery on citrus plant. The study showed that the differences of biopesticide application frequency in citrus plant resulted in different percentage of diplodia stem rot disease recovery. The best treatment was the double application of Phymar C 711 which resulted in highest plant recovery percentage i.e. 72,98% (16 days after application) and 97,92% (32 days after application). Keywords : Anacardium occidentale L., Botryodiplodia theobromae Pat., Citrus reticulata L., biopesticide, Phymar C 711